2017
DOI: 10.1007/s12012-017-9422-2
|View full text |Cite
|
Sign up to set email alerts
|

Diosmin Prevents Isoproterenol-Induced Heart Mitochondrial Oxidative Stress in Rats

Abstract: Cardiac mitochondrial oxidative stress causes mitochondrial damage that plays an important role in the pathology of myocardial infarction. The preventive effects of diosmin on cardiac mitochondrial oxidative stress in isoproterenol-induced myocardial infarcted rats were evaluated. Rats were pretreated with diosmin (10 mg/kg body weight) daily for 10 days. Myocardial infarction was induced in rats by isoproterenol (100 mg/kg body weight) injection twice at an interval of 24 h (on 11th and 12th day). Isoproteren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…No significant difference/observance between the control group and diosmin‐alone group in term of oxidative stress parameter (MDA, NO, SOD, CAT, GSH‐Px, and GSH), biochemical parameters (AST, ALT, ALP, and LDH), histological architecture, body weight, liver weight, and liver weight/body weight ratio ascertained that diosmin did not cause negative effect at the specified dose and duration examined. Findings from diosmin administered at different doses and times, the parameters of oxidative stress (Arab et al, ; Eraslan et al, ; Rehman et al, ; Sharmila Queenthy, Stanely Mainzen Prince, & John, ), biochemical parameters (Eraslan et al, ; Sharmila Queenthy et al, ), liver histology (Eraslan et al, ; Rehman et al, ) findings obtained from this study are consistent with the findings obtained.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No significant difference/observance between the control group and diosmin‐alone group in term of oxidative stress parameter (MDA, NO, SOD, CAT, GSH‐Px, and GSH), biochemical parameters (AST, ALT, ALP, and LDH), histological architecture, body weight, liver weight, and liver weight/body weight ratio ascertained that diosmin did not cause negative effect at the specified dose and duration examined. Findings from diosmin administered at different doses and times, the parameters of oxidative stress (Arab et al, ; Eraslan et al, ; Rehman et al, ; Sharmila Queenthy, Stanely Mainzen Prince, & John, ), biochemical parameters (Eraslan et al, ; Sharmila Queenthy et al, ), liver histology (Eraslan et al, ; Rehman et al, ) findings obtained from this study are consistent with the findings obtained.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, diosmin/diosmetin also has a protective effect against peroxidation by inhibiting the oxidation of cell membrane phospholipids (Villa et al, ). When the previously performed studies involving different compounds with diosmin were evaluated, the oxidative stress parameters (Arab et al, ; Eraslan et al, ; Jain et al, ; Sharmila Queenthy et al, ; Srinivasan & Pari, ; Tahir et al, ; Wojnar, Kaczmarczyk‐Sedlak, & Zych, ), some biochemical parameters (Eraslan et al, ; Sharmila Queenthy et al, ; Tahir et al, ), and liver histopathology (Eraslan et al, ; Rehman et al, ; Srinivasan & Pari, ; Tahir et al, ) similar to those found.…”
Section: Discussionmentioning
confidence: 99%
“…Malonaldehyde (MD) is a major end product formed by lipid peroxidation of polyunsaturated fatty acids during oxidation in cardiomyocyte. Increase in the MD content is an indication of oxidative stress, which progresses to irreversible damage to myocardial muscles, and is seen in ISO-induced myocardial ischemia [45]. Investigations made here indicate animals administered with ISO and left untreated (group II) had significantly elevated levels of MD compared to the control group (group I).…”
Section: Anti-inflammatory Effect Of Rpgmentioning
confidence: 55%
“… 30 The oxidative stress response can cause damage to mitochondria and plays an important role in cardiac pathological processes. 31 The heart is a high oxygen-consuming, high energy-consuming organ. During the course of life, the heart’s orderly diastolic contraction activity relies on cardiomyocytes to increase energy support.…”
Section: Introductionmentioning
confidence: 99%